The Influence of Storage Layout and Material Handling Equipment on Distribution Timeliness in Cross-Docking Operations at PT. Serasi Logistics Indonesia - Setiawan, Djoko Hendro; Rachmat Hidayat, Yusup; Suprayitno, Degdo (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study aims to analyze the influence of storage layout and the use of material handling equipment on the timeliness of distribution in the Crossdocking hub warehouse of PT. Serasi Logistics Indonesia. The main problem faced is inefficiency in the arrangement of the placement of goods and the handling of material equipment which causes delays in delivery, especially in the outbound process. Using a survey-based quantitative method, data was collected through a questionnaire involving respondents related to warehouse operations. Data analysis was carried out by multiple linear regression, t-test for partial significance, F-test for model significance, and determination coefficient (R ²) to measure the relationship between independent variables (storage layout and material handling equipment) and dependent variables (distribution timeliness). The results show that the storage layout and material handling equipment significantly affect the timeliness of distribution, both partially and simultaneously, with a strong contribution to distribution efficiency. The implications of this study highlight the importance of optimizing warehouse layouts and the use of more efficient material handling equipment in improving logistics performance, which can also be a reference for other Crossdocking warehouses.